Translation Method and Meaning Equivalence in The Song Lyric “Let It Go Sung” By Idina Menzel and “Biarkan” By Nadya Almira Puteri - Selfi Aulia Ramadhani; Otong Setiawan Djuharie (INDO PUBLISHING, 2025)
This study aims to analyze the translation method and meaning equivalence in the song lyrics